Pengaruh Layanan Informasi terhadap Motivasi Belajar Siswa MAN 3 Medan - Rizqi Abdullah MPH Panjaitan; Purbatua Manurung; Nurussakinah Daulay (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research aims to examine the influence of information services on student learning motivation at MAN 3 Medan. The research background highlights the importance of guidance and counseling services that help students understand their strengths and weaknesses and accept themselves positively, which is the basis for self-development. The main focus of this research is information services in guidance and counseling, which aims to equip students with knowledge about education, work and personal social development. These services are designed to help students plan and organize their lives more effectively. Learning motivation, which is a driving force from within and outside students to achieve learning goals, is a key aspect in this research. This type of research is Quasi Experiment research with a quantitative type approach. The research results show that the information services provided by guidance and counseling teachers at MAN 3 Medan, in accordance with the service implementation plan, have a positive impact on increasing student learning motivation. Counseling teachers play an important role in supporting and increasing learning motivation through information services, which have proven effective in helping students achieve their academic goals. This research confirms that good information services can significantly increase student learning motivation.